Answer

Verified

472.5k+ views

Hint: First convert out given expression using the formula, ${{\log }_{a}}x=\dfrac{\log a}{\log x} ,\log (cd)=\log c+\log d,\log \left( {{d}^{n}} \right)=n\log d$. Then divide the whole expression by common term. Then transform the obtained expression using ${{\log }_{a}}x=t$, then find the value of ‘t’ and then transform it to get values of x in terms of a.

Complete step-by-step answer:

We are given that for x, a > 0 we have to find the roots of equation

${{\log }_{ax}}a+{{\log }_{x}}{{a}^{2}}+{{\log }_{{{a}^{2}}x}}{{a}^{3}}=0.............\left( i \right)$

Now to proceed the equation we have to use formula such as,

${{\log }_{c}}d=\dfrac{\log d}{\log c}$

By using this we can transform equation (i) as,

$\dfrac{\log a}{\log ax}+\dfrac{\log {{a}^{2}}}{\log x}+\dfrac{\log {{a}^{3}}}{\log {{a}^{2}}x}=0............\left( ii \right)$

Now we will use the formula such as,

log(cd) = log c +log d

By using this we can write equation (ii) as,

$\dfrac{\log a}{\log a+\log x}+\dfrac{\log {{a}^{2}}}{\log x}+\dfrac{\log {{a}^{3}}}{\log {{a}^{2}}+\log x}=0............\left( iii \right)$

Now we will use the formula such as,

$\log \left( {{d}^{n}} \right)=n\log d$

By using this we can write the equation (iii) as,

$\dfrac{\log a}{\log a+\log x}+\dfrac{2\log a}{\log x}+\dfrac{3\log a}{2\log a+\log x}=0............\left( iv \right)$

Now we will divide log a from both numerator and denominator of the term of equation (iv) we get,

$\dfrac{1}{1+\dfrac{\log x}{\log a}}+\dfrac{2}{\dfrac{\log x}{\log a}}+\dfrac{3}{2+\dfrac{\log x}{\log a}}=0...............\left( v \right)$

In equation (v) we will use the formula, $\dfrac{\log c}{\log d}={{\log }_{d}}c$ we get,

$\dfrac{1}{1+{{\log }_{a}}x}+\dfrac{2}{{{\log }_{a}}x}+\dfrac{3}{2+{{\log }_{a}}x}=0..............\left( vi \right)$

Now we will substitute ${{\log }_{a}}x=t$ , we will transform equation (vi) as

\[\dfrac{1}{1+t}+\dfrac{2}{t}+\dfrac{3}{2+t}=0............\left( vii \right)\]

Taking LCM in (vii) we get,

$\dfrac{t\left( 2+t \right)+2\left( 1+t \right)(2+t)+3t\left( t+1 \right)}{\left( 1+t \right)t\left( 2+t \right)}=0$

On cross multiplication we get,

t(2 + t) + 2(1 + t)(2+t) +3t (t + 1) = 0

On further simplification we get,

$\begin{align}

& 2t+{{t}^{2}}+2(2+t+2t+{{t}^{2}})+3{{t}^{2}}+3t=0 \\

& \Rightarrow 2t+{{t}^{2}}+4+2t+4t+2{{t}^{2}}+3{{t}^{2}}+3t=0 \\

\end{align}$

On simplification we get,

$6{{t}^{2}}+11t+4=0$

This is a quadratic equation. We will solve it by splitting the middle term, we get

$\begin{align}

& 6{{t}^{2}}+8t+3t+4=0 \\

& \Rightarrow 2t\left( 3t+4 \right)+1\left( 3t+4 \right)=0 \\

& \Rightarrow (3t+4)(2t+1)=0 \\

& \Rightarrow 3t+4=0,2t+1=0 \\

& \Rightarrow t=-\dfrac{4}{3},t=-\dfrac{1}{2} \\

\end{align}$

So, finally the value for $t=\dfrac{-4}{3},\dfrac{-1}{2}$.

We had assumed,

${{\log }_{a}}x=t$

Substituting the value of ‘t’, we get

${{\log }_{a}}x=\dfrac{-4}{3}$ and ${{\log }_{a}}x=-\dfrac{1}{2}$

Now we will use the transformation that is, ${{\log }_{b}}a=c\Rightarrow a={{b}^{c}}$. By using this in above equation, we get

$x={{a}^{-\dfrac{4}{3}}}$ and $x={{a}^{\dfrac{-1}{2}}}$ respectively.

Therefore, the correct answer is option (a) and (c).

Note: Students should be careful while calculating and finding values of ${{\log }_{a}}x$ also using transformation of changing ${{\log }_{a}}x=t$as $x={{a}^{t}}$.

Another way to solve the quadratic equation is using the formula, $t=\dfrac{-b\pm \sqrt{{{b}^{2}}-4ac}}{2a}$.

Complete step-by-step answer:

We are given that for x, a > 0 we have to find the roots of equation

${{\log }_{ax}}a+{{\log }_{x}}{{a}^{2}}+{{\log }_{{{a}^{2}}x}}{{a}^{3}}=0.............\left( i \right)$

Now to proceed the equation we have to use formula such as,

${{\log }_{c}}d=\dfrac{\log d}{\log c}$

By using this we can transform equation (i) as,

$\dfrac{\log a}{\log ax}+\dfrac{\log {{a}^{2}}}{\log x}+\dfrac{\log {{a}^{3}}}{\log {{a}^{2}}x}=0............\left( ii \right)$

Now we will use the formula such as,

log(cd) = log c +log d

By using this we can write equation (ii) as,

$\dfrac{\log a}{\log a+\log x}+\dfrac{\log {{a}^{2}}}{\log x}+\dfrac{\log {{a}^{3}}}{\log {{a}^{2}}+\log x}=0............\left( iii \right)$

Now we will use the formula such as,

$\log \left( {{d}^{n}} \right)=n\log d$

By using this we can write the equation (iii) as,

$\dfrac{\log a}{\log a+\log x}+\dfrac{2\log a}{\log x}+\dfrac{3\log a}{2\log a+\log x}=0............\left( iv \right)$

Now we will divide log a from both numerator and denominator of the term of equation (iv) we get,

$\dfrac{1}{1+\dfrac{\log x}{\log a}}+\dfrac{2}{\dfrac{\log x}{\log a}}+\dfrac{3}{2+\dfrac{\log x}{\log a}}=0...............\left( v \right)$

In equation (v) we will use the formula, $\dfrac{\log c}{\log d}={{\log }_{d}}c$ we get,

$\dfrac{1}{1+{{\log }_{a}}x}+\dfrac{2}{{{\log }_{a}}x}+\dfrac{3}{2+{{\log }_{a}}x}=0..............\left( vi \right)$

Now we will substitute ${{\log }_{a}}x=t$ , we will transform equation (vi) as

\[\dfrac{1}{1+t}+\dfrac{2}{t}+\dfrac{3}{2+t}=0............\left( vii \right)\]

Taking LCM in (vii) we get,

$\dfrac{t\left( 2+t \right)+2\left( 1+t \right)(2+t)+3t\left( t+1 \right)}{\left( 1+t \right)t\left( 2+t \right)}=0$

On cross multiplication we get,

t(2 + t) + 2(1 + t)(2+t) +3t (t + 1) = 0

On further simplification we get,

$\begin{align}

& 2t+{{t}^{2}}+2(2+t+2t+{{t}^{2}})+3{{t}^{2}}+3t=0 \\

& \Rightarrow 2t+{{t}^{2}}+4+2t+4t+2{{t}^{2}}+3{{t}^{2}}+3t=0 \\

\end{align}$

On simplification we get,

$6{{t}^{2}}+11t+4=0$

This is a quadratic equation. We will solve it by splitting the middle term, we get

$\begin{align}

& 6{{t}^{2}}+8t+3t+4=0 \\

& \Rightarrow 2t\left( 3t+4 \right)+1\left( 3t+4 \right)=0 \\

& \Rightarrow (3t+4)(2t+1)=0 \\

& \Rightarrow 3t+4=0,2t+1=0 \\

& \Rightarrow t=-\dfrac{4}{3},t=-\dfrac{1}{2} \\

\end{align}$

So, finally the value for $t=\dfrac{-4}{3},\dfrac{-1}{2}$.

We had assumed,

${{\log }_{a}}x=t$

Substituting the value of ‘t’, we get

${{\log }_{a}}x=\dfrac{-4}{3}$ and ${{\log }_{a}}x=-\dfrac{1}{2}$

Now we will use the transformation that is, ${{\log }_{b}}a=c\Rightarrow a={{b}^{c}}$. By using this in above equation, we get

$x={{a}^{-\dfrac{4}{3}}}$ and $x={{a}^{\dfrac{-1}{2}}}$ respectively.

Therefore, the correct answer is option (a) and (c).

Note: Students should be careful while calculating and finding values of ${{\log }_{a}}x$ also using transformation of changing ${{\log }_{a}}x=t$as $x={{a}^{t}}$.

Another way to solve the quadratic equation is using the formula, $t=\dfrac{-b\pm \sqrt{{{b}^{2}}-4ac}}{2a}$.

Recently Updated Pages

How many sigma and pi bonds are present in HCequiv class 11 chemistry CBSE

Mark and label the given geoinformation on the outline class 11 social science CBSE

When people say No pun intended what does that mea class 8 english CBSE

Name the states which share their boundary with Indias class 9 social science CBSE

Give an account of the Northern Plains of India class 9 social science CBSE

Change the following sentences into negative and interrogative class 10 english CBSE

Trending doubts

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Difference Between Plant Cell and Animal Cell

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

At which age domestication of animals started A Neolithic class 11 social science CBSE

Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE

Summary of the poem Where the Mind is Without Fear class 8 english CBSE

One cusec is equal to how many liters class 8 maths CBSE

Give 10 examples for herbs , shrubs , climbers , creepers

Change the following sentences into negative and interrogative class 10 english CBSE